Usulan Perbaikan Tata Letak Raw Material Cable pada Gudang Pusat Menggunakan Metode ABC di PT X - Mulya, Ulwan Adi; Rahmawati, Nur (LPPM Universitas Pahlawan Tuanku Tambusai, 2025)
The Central Warehouse of PT X serves as a storage facility for raw materials prior to shipment to users or production sites. The vast quantity of production materials necessitates optimal storage space to ensure proper storage. Effective material management and placement significantly impact storage capacity. This study aims to optimize raw material cable layout at the central warehouse using the ABC method. Analysis involves categorizing materials by size and priority, facilitating efficient handling and management. Results show a 17.5% reduction in overall material storage space and significant improvements in spatial efficiency. The proposed layout design enhances operator inspection and mobility while minimizing error and injury risks. This research contributes to developing effective, efficient and sustainable logistics and warehouse management strategies.